Defect Detection of Topside Offshore Platform Structure Using Non-Destructive Testing Methods - Mahmod, Muhammad Faisal; Nazrin Yacub, Farah (Journal of Advanced Mechanical Engineering Applications, 2024)
Non-destructive testing on offshore rigs involves multiple sections. The topside platform structure, which consists of the main deck, cellar, and sub-cellar deck, is one of the most important sections. The purpose of this research is to use appropriate nondestructive testing (NDT) methods to assess the internal and surface defects as well as identify the material properties of the selected structure at the topside platform structure. Various NDT technologies can be utilized to detect faults on the topside of the offshore platform. The NDT techniques used in this study are ultrasonic, magnetic particle, and dye penetrant testing. To describe the material in the samples, a different method known as positive identification material is employed. Four tasks are involved in this process: identifying the material properties of each sample, identifying surface and interior faults, and comparing the two types of defects. The results of the analysis revealed that a 316L stainless steel specimen contained as much as 19.2% chromium, 11.8% nickel, and 3.0% molybdenum. Magnetic particle inspection was recommended for surface and subsurface inspection. In contrast, the ultrasonic testing examination yielded the best outcome for the topside offshore platform's interior problem.